Reviewing research on flow in school setting - Kee, Chong Wei; Mohd Hashim, Intan Hashimah (2014)
Flow refers to a psychological state in which people are undergoing optimal experience during a particular activity. Specifically, people who experience flow are happy, cognitively efficient, and motivated at the same time.The concept of flow has begun to be widely applied in school setting ever since it was established. However, limited work has focused on systematic review of the current trend of the literature.The aim of this paper is to review published studies on flow within the school setting.A total number of 233 research studies including journals, journal’s articles, dissertations, and books that are related to flow has been reported in various academic databases.Various research studies that are related to flow in school setting have been reviewed to understand the contemporary trend.In depth discussion on specific academic exercises (e.g., writing, reading, and teaching) has been selected as one of the major focuses in this review.The limitations in term of research development of flow in school setting are also discussed.